Positive & Negative Roles of Innate Effector Cells in Controlling Cancer Progression - Stolk, Dorian; van der Vliet, Hans J.; de Gruijl, Tanja D.; van Kooyk, Yvette; Exley, Mark A. (Frontiers in Immunology, 2018)
Innate immune cells are responsible for the front line of host defense against pathogens and now appear to have a range of non-infectious roles as well, especially in cancer. Establishing the balance of innate immune responses is critical for the ‘flavor’ of these responses and subsequent adaptive immunity and can be either ‘good’ or ‘bad’ in controlling cancer progression. The importance of innate lymphocytic NK cells in tumor immune responses has already been extensively studied in the last few decades, but more recently several relatively oligo-clonal or semi-invariant innate T cells received substantial interest in tumor immunology, including invariant natural killer T (iNKT), γδ-T and mucosa associated invariant T (MAIT) cells. These subsets produce high levels of various pro- and/or anti- inflammatory cytokines/chemokines, reflecting their capacity to suppress or stimulate immune responses. Cancer patient survival has been linked to NK, iNKT and γδ-T cell activity and these innate subsets as well as MAIT cells have physiological roles in anti- tumor responses, emphasizing their relevance in tumor immunity. A variety of clinical trials has focused on manipulating NK, iNKT and γδ-T cell functions as a cancer immunotherapeutic approach demonstrating their safety and potential for achieving benecial therapeutic effects, while implications for MAIT cell-related therapies are still in their infancy. Current issues limiting the full therapeutic potential of these innate cell subsets appear to be related to (e.g.) defects and suppressive properties of these subsets that, with the right stimulus, might be reversed. In general, how innate lymphocytes are activated appears to control their subsequent abilities and consequent impact on adaptive immunity. Controlling these potent ‘Special Forces’ of the immune system should enable their protective roles to dominate and their deleterious potential (in the specific context of cancer or other diseases) to be mitigated.